Pengaruh Pajak Daerah, Retribusi Daerah, terhadap Kemampuan keuangan Daerah Kabupaten Gorontalo - Saprudin, Saprudin (Gorontalo Accounting Journal, 2018)
This study aims to identify, analyze, test and provide empirical evidence as to what the relationship variables Local Taxes, Levies, on Financial Capability.Type This research is associative which aims to determine the relationship between two or more variables, relations who want to study in this study is causal (causal) to analyze the relationships between the variables with other variables and how a variable affects other variables.Research Shows that one). Local Taxes positive effect on the ability of the Regional Financial Daerah.2). Retribution positive effect on the ability of the Regional Local Finance rejected. Levies according to Law No. 34 of 2000 is local charges as payment for specific services or special licensing is provided and / or supplied by the local government for the benefit of private persons or entities. Equal to the tax, retribution is also a positive influence on the Regional Financial Capability area.